Análise e caracterização da urbanização na área de recarga do Aqüífero Guarani na cidade de Ribeirão Preto SP - Olaia, Flávia Buischi (Universidade Federal de São Carlos, 2005)
The present study is an analysis and characterization of the urbanization of the area of arenite surfacing of Botucatu/Pirambóia, a recharge area of the Guarani Freatic Sheet in the city of Ribeirão Preto - SP. The main objective was to survey the urbanization of the area in terms of soil use and occupation, identifying the possible existing negative impacts that might compromise this important underground water source in quantitative and qualitative terms. After this survey, the intention is to propose measures that will mitigate the impacts detected, as well as directives for soil subdivision in the region of recharge of the freatic sheet which involves 40% of the city of Ribeirão Preto-SP. A further objective is to provide environmental conservation and the maintenance of quality of life and of the environment integrated in the process of use and occupation of the existing soil and in the specific needs of the local environment by means of measurese for the control and prevention of possible polluting agents and environmental degradation. The intention is to guarantee the best environmental and living conditions to the population and to preserve and conserve the magnificent water resource represented by the Guarani Freatic Sheet by raising the awareness of Public Authorities and of society about the severe reduction of fresh water stores in the planet, the indiscriminate use, the contamination, the pollution and the degradation of underground water sources and the consequences that all of the problems will have for the near future of humankind. The city of Ribeirão Preto is fully supplied by this water source which, because of the conditions of its occurrence anf of its quality standard should be considered a noble resource worthy of preservation, conservation and awareness of public authoritiues and of the population of the city. According to the environmental zoning of Ribeirão Preto, large part of the city is located in the area of recharge of the Guarani Freatic Sheet, with various negative impacts generated by the use and occupation of the soil in these areas in an improper and disorderly manner. Thus, it is clear that it is important to implement an Environmental Management of Underground Water in the Botucatu Area of Arenite Surfacing and of the recharge of the Guarani Freatic Sheet in Ribeirão Preto
Keywords: Planejamento urbano; Recursos hídricos; Águas subterrâneas; Sustentabilidade ambiental urbana; Avaliação de impacto ambiental; Degradação urbana; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::AGUA